Fiberglass-reinforced glulam beams: Mechanical properties and theoretical model - Fiorelli, Juliano [UNESP]; Dias, Antonio Alves (FapUNIFESP (SciELO), 2006)
The glued-laminated lumber (glulam) technique is an efficient process for making rational use of wood. Fiber-Reinforced Polymers (FRPs) associated with glulam beams provide significant gains in terms of strength and stiffness, and also alter the mode of rupture of these structural elements. In this context, this paper presents a theoretical model for designing reinforced glulam beams. The model allows for the calculation of the bending moment, the hypothetical distribution of linear strains along the height of the beam, and considers the wood has a linear elastic fragile behavior in tension parallel to the fibers and bilinear in compression parallel to the fibers, initially elastic and subsequently inelastic, with a negative decline in the stress-strain diagram. The stiffness was calculated by the transformed section method. Twelve non-reinforced and fiberglass reinforced glulam beams were evaluated experimentally to validate the proposed theoretical model. The results obtained indicate good congruence between the experimental and theoretical values.
Keywords: FRP; Glued-laminated lumber; Strain; Computational methods; Glass fiber reinforced plastics; Mathematical models; Mechanical properties; Strain measurement; Stresses; Fiber-reinforced polymers (FRPs); Fiberglass-reinforced glued-laminated lumber beams; Glued laminated lumber; Stress-strain diagram; Lumber; Computation; Glass Fibers; Mathematical Models; Mechanical Properties; Polymers; Strains